2016
DOI: 10.1039/c5sm03139g
|View full text |Cite
|
Sign up to set email alerts
|

The glycocalyx promotes cooperative binding and clustering of adhesion receptors

Abstract: Cell adhesion plays a pivotal role in various biological processes, e.g., immune responses, cancer metastasis, and stem cell differentiation. The adhesion behaviors depend subtly on the binding kinetics of receptors and ligands restricted at the cell-substrate interfaces. Although much effort has been directed toward investigating the kinetics of adhesion molecules, the role of the glycocalyx, anchored on cell surfaces as an exterior layer, is still unclear. In this paper, we propose a theoretical approach to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Dynamically, a recent study found that in the presence of glycocalyx, the binding kinetics of nascent and mature focal adhesions is in good agreement with the Monte Carlo simulation (see below for an explanation of the Monte Carlo simulation). The study also indicated that higher thickness and rigidity of glycocalyx decreases binding affinity at the nascent adhesion site but does not affect mature adhesions, effectively remobilizing integrins from new, unstable adhesions into mature adhesions 87. Over the past half century, research into focal adhesion biology has provided a myriad of insights into its constituents, functions, and roles in pathology.…”
Section: Integrin Dynamics and Mechanotransductionmentioning
confidence: 86%
“…Dynamically, a recent study found that in the presence of glycocalyx, the binding kinetics of nascent and mature focal adhesions is in good agreement with the Monte Carlo simulation (see below for an explanation of the Monte Carlo simulation). The study also indicated that higher thickness and rigidity of glycocalyx decreases binding affinity at the nascent adhesion site but does not affect mature adhesions, effectively remobilizing integrins from new, unstable adhesions into mature adhesions 87. Over the past half century, research into focal adhesion biology has provided a myriad of insights into its constituents, functions, and roles in pathology.…”
Section: Integrin Dynamics and Mechanotransductionmentioning
confidence: 86%
“…Similar regulation has been observed with LYVE-1 [ 20 ], an HA receptor homologous to CD44. Furthermore, the high molecular weight HA has been shown to induce the aggregation of CD44 receptors, while low molecular weight HA seems to lack this ability [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Calculations and simulations with discretized elastic-membrane models indicate segregation of sterically repulsive proteins of length l r and receptor-ligand complexes with preferred local separation l 0 < l r if the concentration of the repulsive proteins exceeds the critical concentration c r k B T /κ ef (l r − l 0 ) 2 with a numerical prefactor c r [27]. The interplay of receptor-ligand binding and steric repulsion from glycocalyx proteins has also been investigated in models for the clustering of integrin receptors during cell adhesion [75,[134][135][136]. In addition, segregation of long and short bonds has been observed in experiments with reconstituted membranes that adhere via anchored DNA [137].…”
Section: Cooperative Protein Binding From Membrane Shape Fluctuationsmentioning
confidence: 99%